Precollege and New-Onset College Interpersonal Trauma as Predictors of Baseline and Changes in Alcohol Use Disorder Symptoms During College - Bountress, Kaitlin E. (Journal of interpersonal violence, 2021)
College is a high-risk time for interpersonal trauma (IPT) exposure (e.g., physical or sexual abuse/assault), a potent form of trauma exposure. College is also a high-risk time for alcohol misuse, as use begins and increases in adolescence and peaks in the early/mid-20s. In addition, although IPT is associated with alcohol misuse, less clear is whether distal (prior to college) or proximal (during college) IPT impacts alcohol use disorder (AUD) symptoms at the beginning of college and/or changes in symptoms during college. Data were collected from a large, longitudinal study of college students, attending a large public university in the southeast, who had reported lifetime IPT as well as lifetime alcohol use. Participants in the current study were 18.5 years old (SD = 0.46), primarily female (67.2%), and of diverse racial backgrounds (e.g., 53.4% White, 18.5% Black, 12.7% Asian, 15.4% Other). Latent change score analyses were employed to test the impact of IPT prior to college and IPT during college on initial levels of, and changes in, AUD symptoms during college. Those who experienced an IPT prior to college reported more AUD symptoms at the beginning of college and less changes in AUD symptoms during the first year of college. Those who experienced an IPT in the first 2 and last 2 years of college reported greater increases in symptoms in the first 2 and last 2 years of college, respectively. Findings suggest that prevention and intervention efforts for those who experience an IPT prior to or during college may be useful in reducing AUD symptoms during that time period.